Finding your way in a wild new world : reclaim your true nature to create the life you want - Beck, Martha Nibley, 1962- (Free Press, 2011)
Many people feel called to help others and change the world, but they just don't know how to fulfill their potential. They have the creativity and passion, but often get lost, not knowing how to direct their energies. Life coach Martha Beck shows how readers can find their calling in service and healing--while realizing their destiny.